Optimizing Search Engine Optimization (SEO) and User Experience (UX) on Local Online Business Training Websites: A Comparative Study of Young Entrepreneur Community Platforms - Nurrohman, Rosyid (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
Digitalization has significantly transformed the delivery of online business training, particularly for young entrepreneurs. However, gaps remain between website visibility on search engines and the user-friendliness of online learning features. This study aims to compare the quality of search engine optimization and user experience across two local online business training websites operated by young entrepreneur communities. A qualitative approach with a comparative study design was employed. Data were collected through in-depth observations of website structure, interface, and semi-structured interviews on 34 respondents who had previously used one or both platforms. Respondents were selected using purposive sampling based on relevant user experience criteria. Thematic analysis was conducted to identify patterns in user interaction and SEO practices implemented by each platform. The findings reveal that each website demonstrates distinct strengths: one excels in consistent link structure and systematic keyword utilization, while the other offers a cleaner interface and more intuitive navigation. This study contributes a user-centered and content-effectiveness-based evaluation framework, which may serve as a reference for online business training website developers in designing platforms that are not only digitally accessible but also responsive to the evolving needs of young users in a sustainable manner.